TRAVAIL SUR LE FAITS-DIVERS: ACTIVITÉ DE LA COMPRÉHENSION ÉCRITE - Agustiningrum, Tri Eko (Universitas Negeri Semarang, 2010)
In the teaching of reading comprehension, there are many different strategies that can be used to simplify the process of teaching. The determination to selec teaching strategies is not arbitrary, but should be considered from various aspects. There are a number of strategies that can be applied to improve the studentsÃ¢â‚¬â„¢ comprehension. The strategies are designed to help teachers bring knowledge about learners, guide learners to read the text, help them develop active and focused reading activities, and strengthenÃ‚Â the them in conceptualizing ideas taken from the reading text. One type of readings that can be used is authentic or original text not to be made for the benefit of foreign language teaching. The goal was to determine the ability of language learners to analyze the text. Key Words: reading comprehension, authentic material, teaching strategies